Writings from the Margins: German-Jewish Women Poets from the Bukovina - Amy Colin (Studies in 20th & 21st Century Literature, 1997)
Emerging at the crossroads of heterogeneous languages and cultures, German-Jewish women's poetry from the Bukovina displays the characteristics of its fascinating multilingual contextuality, yet it also bears the stigma of a double marginalization, for its representatives became time and again targets of both anti-Semitic attacks as well as gender discrimination. The present essay explores the untiring struggles of German-Jewish women authors from the Bokovina for acceptance within the Jewish and non-Jewish community. It analyzes their attempts to cope with social barriers, prejudices, and their difficult situation as both women and Jews. The essay also sets their poetry against the background of their multilingual contextuality. It is the Bukovinian biotope, where Ruthenians, Romanians, Germans, Jews, Armenians, Magyars, Poles, Lipovanes, and Hutsuls peacefully coexisted for many centuries, producing a variegated Romanian, Ruthenian, Austro-German, German-Jewish, and Yiddish literature as well as poets who were fluent in several languages.
Keywords: heterogeneous languages; heterogeneous cultures; culture; language; German-Jewish women' s poetry; German-Jewish; women; poetry; Bukovina; multilingual contextuality; double marginalization; anti-Semitic; gender discrimination; German-Jewish women authors; acceptance; struggle; Jewish community; non-Jewish community; social barriers; prejudices; Ruthenians; Romanians; Germans; Jews; Armenians; Magyars; Poles; Lipovanes; Hutsuls; coexisted; Romanian literature; Ruthenian literature; Austro-German literature; German-Jewish literature; Yiddish literature; poets; fluent